Zen and the art of the monologue - Sankey, Jay, 1963- (Routledge, 2000)
Jay Sankey--stand-up comic, magician, and cartoonist--is back with another book for performers. Building on the success of his Zen and the Art of Stand-up Comedy, Jay is moving further into the uncharted wilds of solo performance.